News and narratives: A cointegration analysis of Russian economic policy uncertainty - Andrea Boitani; Catalin Dragomirescu-Gaina (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2022)
Russia has become more integrated and therefore significantly dependent on global developments over the last decades, despite being ruled by an increasingly autocratic regime. How does Russian media cover the associated economic and policy challenges? To answer, we use the economic policy uncertainty indexes as proxies for media coverage, together with a limited set of variables reflecting both domestic and international developments. Our main findings come from a VEC model estimated with two cointegrating vectors, encompassing two long-term equilibria. A first cointegrating vector describes the domestic political context, highlighting the key role that media coverage can play in supporting autocratic regimes. While the second cointegrating vector is associated with international developments, portraying swings in global risk appetite, we find that deviations from it can, too, drive popular support for the incumbent president. To see more precisely how Russian media coverage can be used as a policy instrument, we employ several narrative proxies and find that (only in the short run) some of these might be used to exert control and influence, while others to justify policy errors or successes.
Keywords: C50; D80; F50; P50; 330; Economic policy uncertainty; media coverage; cointegration analysis